Plant hormones: on-the-spot reporting - Waadt, Rainer (Nature plants, 2015)
The development of a new jasmonate reporter further extends the tools that add greater detail to the investigation of plant hormones. Such reporters for the various types of plant hormones, exploiting different aspects of their activity, will help us to eventually study hormone signalling, distribution and dynamics in intact tissue.